Biological Properties of JNK3 and Its Function in Neurons, Astrocytes, Pancreatic β-Cells and Cardiovascular Cells - Nakano, Rei (Cells, 2020)
JNK is a protein kinase, which induces transactivation of c-jun. The three isoforms of JNK, JNK1, JNK2, and JNK3, are encoded by three distinct genes. JNK1 and JNK2 are expressed ubiquitously throughout the body. By contrast, the expression of JNK3 is limited and observed mainly in the brain, heart, and testes. Concerning the biological properties of JNKs, the contribution of upstream regulators and scaffold proteins plays an important role in the activation of JNKs. Since JNK signaling has been described as a form of stress-response signaling, the contribution of JNK3 to pathophysiological events, such as stress response or cell death including apoptosis, has been well studied. However, JNK3 also regulates the physiological functions of neurons and non-neuronal cells, such as development, regeneration, and differentiation/reprogramming. In this review, we shed light on the physiological functions of JNK3. In addition, we summarize recent advances in the knowledge regarding interactions between JNK3 and cellular reprogramming.